Straw composting using earthworm (Eudrilus eugeniae) and fungal inoculant (Trichoderma viridae) and its utilization in rice (Oryza sativa)-groundnut (Arachis hypogaea) cropping system - SARANGI, S K; LAMA, T D (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted at ICAR Research Complex for North Eastern Hill (NEH) Region, India during 2007–09 on composting of paddy straw and its effect on rice (Oryza sativa L.)-groundnut (Arachis hypogaea L.) cropping system. The composting experiment consisted of eight treatments (i) Eudrilus eugeniae, (ii) E. eugeniae + 2.5% lime, (iii)E. eugeniae + 5.0% lime, (iv) E. eugeniae + 7.5% lime, (v) Trichoderma viridae, (vi) T. viridae + 2.5% lime, (vii) T.viridae + 5.0% lime, (viii) T. viridae + 7.5% lime. The composting was faster (67 days) and multiplication of earthworm was highest (22 times) with earthworm + 5.0% lime. There was a positive effect of lime application on the pH of the compost and it increased from 6.24 to 7.09 due to application of 5.0% lime to the composting substrate. The field experiment consisted of 11 treatments, viz. eight composts produced from composting experiment @ 6 tonnes/ha, farmyard manure (FYM) @ 6 tonnes/ha, recommended dose of fertilizer (80-26.2-33.3 kg N-P-K/ha) and control. Soil moisture in 0-15 cm layer increased by 3.06%, pH changed from acidic to neutral and soil organic carbon increased by 0.39% due to application vermicompost. Addition of vermicompost prepared with 5% lime increased the soil microbial biomass carbon by 147% over control, while 51% increase was recorded with application of T. viridae compost with 2.5% lime. The grain and pod yields of upland rice and groundnut increased by 120% and 107% respectively over control due to application of vermicompost prepared with 5.0% lime.